Soybean seed germinattion and seedling growth in response to deterioration and priming: effect of seed size - Moshtaghi-Khavaran, Amir; Khomari, Saeid; Zare, Naser (Plant Breeding and Seed Science, 2014)
A laboratory experiment was conducted to determine if separation of soybean [Glycine max (L.) Merr.] seeds by size might be effective in germinability of aged and primed seeds and subsequent seedling vigour. A known soybean seed lot was separated into four size classes using round-hole screens. The seed lots were deteriorated by rapid aging and invigorated by hydro- and halo-priming. These pre-treated seeds were planted in rolled paper towels and the results were evaluated according to ISTA rules. The small soybean seeds had higher speed of germination than the other size classes. The seedlings produced from large and medium seeds were longer and heavier than those from other size classes. Our results indicated that the large seeds had less sensitivity to short-term aging condition owing to the number of normal seedlings, while the deterioration more increased the germination time of large and medium seeds, compared to small ones. The alleviatory effects of halo-priming on deterioration of seeds are greater compared with hydro-priming. Although there are some debates, the present data further indicate that larger soybean seeds are susceptible to aging condition.